2010
DOI: 10.1007/s11010-010-0571-x
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of stearoyl-CoA desaturase 1 and elongase 6 genes expression in rat lipogenic tissues by chronic food restriction and chronic food restriction/refeeding

Abstract: Successful treatment of obesity and related diseases by chronic food restriction requires the understanding of the effect of such nutritional therapy on the expression of genes which have been implicated to be involved in some diseases associated with obesity. The purpose of this study was to examine the effect of chronic food restriction and chronic food restriction/refeeding on lipogenic enzymes, especially the expression of genes encoding the stearoyl-CoA desaturase 1 (Scd1) and elongase6 (Elovl6) in rat li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 33 publications
5
31
0
Order By: Relevance
“…20,21) Manipulation of the diet increases the activity of lipogenic enzymes, which are present in the liver and adipose tissue. 22) This activity is reduced due to the FAs derived from food. 23) Frequently, authors noted the stabilization of lipogenesis process.…”
Section: Resultsmentioning
confidence: 99%
“…20,21) Manipulation of the diet increases the activity of lipogenic enzymes, which are present in the liver and adipose tissue. 22) This activity is reduced due to the FAs derived from food. 23) Frequently, authors noted the stabilization of lipogenesis process.…”
Section: Resultsmentioning
confidence: 99%
“…Males and females were housed in individual wire-mesh cages, in the same room at 22°C, under a light:dark 12h:12h cycle with lights on at 7:00 a.m. The animals were allowed free access to tap water and food (the commercial diet composition was described in [22]). The amount of consumed food was measured every other day.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…The animals were treated as described recently [15]. Briefly, the rats were divided randomly into 2 groups.…”
Section: Animalsmentioning
confidence: 99%
“…The information about the effect of food restriction and food restriction/refeeding on Scd1 and Elovl6 gene expressions in adipose tissue depots could be of great importance because food restriction is often practiced by individuals trying to lose body weight as well as in prevention of insulin resistance and type 2 diabetes [13]. It has recently been shown that 50% food restriction exerts different effects on Scd1 mRNA level in various adipose tissue depots (no effect on epididymal adipose tissue, down regulation of retroperitoneal fat [14] and up regulation in perirenal adipose tissue [15]). These contradictory results led us to examine the effect of prolonged food restriction and prolonged food restriction/refeeding on Scd1 and Elovl6 gene expressions in main body depots of rat white adipose tissue.…”
Section: Introductionmentioning
confidence: 99%